2016
DOI: 10.1155/2016/5830103
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cell Treatment Induces Specific Alloantibodies in Horses

Abstract: Background. It is unknown whether horses that receive allogeneic mesenchymal stem cells (MSCs) injections develop specific humoral immune response. Our goal was to develop and validate a flow cytometric MSC crossmatch procedure and to determine if horses that received allogeneic MSCs in a clinical setting developed measurable antibodies following MSC administration. Methods. Serum was collected from a total of 19 horses enrolled in 3 different research projects. Horses in the 3 studies all received unmatched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 25 publications
7
74
2
Order By: Relevance
“…Recent study has suggested that allogeneic stem cells may elicit an immune response in a recipient animal and that allogeneic donor MSCs are not fully immune-privileged, as previously claimed. 41 by controlling cytokine signalling and matrix remodelling, which was consistent with our results. Moreover, it was shown that DNAdemethylation was associated with the induction of the TET gene expression, which initiated the conversion of nuclear 5-methylcytosine (5 mC) to 5-hydroxymethylcytosine (5 hmC).…”
Section: Discussionsupporting
confidence: 93%
“…Recent study has suggested that allogeneic stem cells may elicit an immune response in a recipient animal and that allogeneic donor MSCs are not fully immune-privileged, as previously claimed. 41 by controlling cytokine signalling and matrix remodelling, which was consistent with our results. Moreover, it was shown that DNAdemethylation was associated with the induction of the TET gene expression, which initiated the conversion of nuclear 5-methylcytosine (5 mC) to 5-hydroxymethylcytosine (5 hmC).…”
Section: Discussionsupporting
confidence: 93%
“…It is plausible that an innate immune reaction to the ASCs and/or alloantibody production may have reduced ASC survival time and impeded their immunomodulatory effect which in turn also reduced the success rate and prolonged the clinical response . This is in agreement with previous studies that demonstrated that allogenic ASCs do not completely evade immune surveillance .…”
Section: Discussionsupporting
confidence: 88%
“…We were able to detect specific antibody development in one out of the five cats tested. This alloantibody formation in cats parallels and confirms what has been noted in many species including horses, pigs, macaques, rats and humans [38,41,[45][46][47][48][49]. Nonetheless, the significance of antibody development, in terms of clinical outcome, is hotly debated as many of these animals and humans show clinical improvement in spite of antibody development.…”
Section: Discussionsupporting
confidence: 82%
“…Increasing body of evidence suggests that allogeneic MSCs may elicit an immune response in a recipient animal and that allogeneic donor MSCs are not fully immune‐privileged, as previously claimed. The formation of anti‐allogeneic MSC antibodies, following an intradermal allogeneic MSC injection, was observed in horses . These results highlight the potential risk of allogeneic MSC application.…”
Section: Introductionmentioning
confidence: 70%